DEVELOPMENT OF PBL-BASED PHYSICS LEARNING E-MODULE ON MECHANICAL WAVE MATERIAL IN CLASS XI - Malau, Kristian; Purwanto, Purwanto (UNIVERSITAS NEGERI MEDAN, 2023)
This research aims to (1) produce a physics module on the topic of Mechanical Waves thatmeets the criteria of validity, practicality, and effectiveness for implementation in the physics learning process, (2) determine the validity level of the physics learning e-module based on Problem Based Learning on the topic of Mechanical Waves for 11th-grade students at SMA Negeri 11 Medan, (3) determine the practicality level of the physics learning e-module based on Problem Based Learning on the topic of Mechanical Waves for 11th-grade students at SMA Negeri 11 Medan, (4) determine the effectiveness level of the physics learning e-module based on Problem Based Learning on the topic of Mechanical Waves for 11th-grade students at SMA Negeri 11 Medan. The subjects of this research were 32 students of class XI MIA 3 at SMA Negeri 11 Medan. This study employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The instruments used in this research consisted of expert validation questionnaires, media expert validation questionnaires, questionnaires on student responses to the physics learning module based on Problem Based Learning on the topic of Mechanical Waves for 11th-grade students at SMA, and a test instrument. The data analysis technique used in this research was descriptive analysis. The results of this research are as follows: (1) a physics module on the topic of Mechanical Waves based on Problem Based Learning has been developed and validated by two experts with excellent validity, (2) the practicality level of the physics module on the topic of Mechanical Waves based on Problem Based Learning that has been developed is highly practical, (3) the effectiveness level of the physics module on the topic of Mechanical Waves based on Problem Based Learning that has been developed is categorized as moderate.